Desain dan Implementasi Mobile Kuliah di Politeknik Negeri Lampung Berbasis Teknologi Android - Henry Kurniawan; Tri Sandhika Jaya (Jurnal Ilmiah ESAI, 2016)
The development of technology has created the development of innovation in learning. In the middle of the development of learners get in touch with the mobile device and Internet technology becomes a new trend that enables mobile learning, or better known as mobile learning (m-learning). Lampung State Polytechnic is a university that focuses every effort on developing the quality of education. Currently Lampung State Polytechnic has not yet taken advantage of e-learning. E-Learning can be optimized by combining m-learning to e-learning, where there is an alternative learning process to be done with computers or mobile devices or combined with conventional learning system. Based on these issues, this study was made to develop m-lecture with Android platform based.Â Keywords: mobile learning, e-learning, m-lectures, mobile devices, m-learning, android